SOW MILK YIELD AND COMPOSITION IN RELATION TO DAM AND LITTER PERFORMANCE (1976)
A total of 100 sows involving seven pure and crossbred genotypes of the Large White, Landrace, indigenous pigs of Nigeria and the Duroc x Large White, Duroc x Landrace and reciprocal crosses between the Large White and Landrace were used. The study embraced the milk production, milk composition and the performances of both sows and their litters. Results obtained indicate that milk production was quite low with the average eight week production of 73.99 kg of the indigenous sow to 153.21 kg of the Duroc x Large White crosses. However, percentage milk constituents were quite high with values of 19-23%, total solids, 7 - 9.2% fat, 6.9 - 7.5% protein, 4.6 - 6.0% Lactose, 0.7 - 0.9%, 0.19 - 0.35% Calcium and 0.11 - 0.20% phosphorus in both colostrum and milk. The yield of milk nutrients were similarly high, namely protein 92-175, fat 119—228 and total solids 291—576 g/sow/day and a corresponding yield of protein of 306 - 334, and fat 310 - g/kg dry matter. Litter size and litter weights at birth were quite comparable with what obtains under temperate conditions yet litter weaning weights were suboptimal in the range of 4.4 - 10 kg per piglet at eight weeks. Contrarily efficiency of milk utilization was very high and in the neighbourhood of 4 - 6 kg milk per kilogram weight gained for the pure bleeds and 2 -3 kg for the crossbreeds. Milk yield per metabolic body size was insignificantly different with values of 3.7 - 4.3 kg recorded. A high phenotypic correlation between milk and body weight at farrow could be a measure of increasing milk production of the smaller bodied indigenous pigs through selection for body size While the crossbred sows outweighed the pure breeds in their reproductive performance, all breeds suffered from seasonal fluctuation which depresses the milk production and reproductive efficiency. It can be stated that milk production of the sow is not the only limiting factor to higher productivity under the tropical condition. It is a combination of environment and management procedures in that seasonal depression has been implicated in most of the traits studied. Another major contributing factor has been the sub-clinical level of hygiene under which the animals exist. Reports have indicated that crossbreds are less susceptible to performance problems when they are bred and selected in the environments in which they are expected to perform as borne out by the results of this study. Crossbreeding might be a solution to most of these breeding problems especially by incorporating favourable genes of adaptation, disease resistance and some yet to be discovered traits in our indigenous pigs with those of the exotic purebred to develop a new breed of pig in the tropics for the tropics. The results were therefore discussed in the light of superiority of crossbreeding and adaptation of the indigenous sow.